Persisting Rise in Referrals During Labor in Primary Midwife‐led Care in The Netherlands. Issue 3 (18th September 2013) - Offerhaus, Pien M.; Hukkelhoven, Chantal W.P.M.; de, Ank; van der, Karin M.; Scheepers, Peer L.H.; Lagro‐Janssen, Antoine L.M.
Abstract Background There are concerns about the Dutch maternity care system, characterized by a strict role division between primary and secondary care. The objective of this study was to describe trends in referrals and in perinatal outcomes among labors that started in primary midwife‐led care. Methods We performed a descriptive study of all 789, 795 labors that started in primary midwife‐led care during 2000 to 2008 in The Netherlands. Referrals to obstetrician‐led care or pediatrician were classified as urgent or nonurgent. Perinatal safety was described by perinatal mortality (intrapartum or neonatal 0–7 days), admission to neonatal intensive care unit 0–7 days, and Apgar score < 7 at 5 minutes. Results The proportion of referrals during labor or after birth declined from 52.6 to 42.6 percent for nulliparous women and from 83.2 to 76.7 percent for multiparous women. Especially nonurgent referrals during the first stage increased, for nulliparous women from 28.7 to 40.7 percent and for multiparous women from 10.5 to 16.5 percent. Referrals were less frequent in planned home births. Perinatal mortality was 0.9 per thousand births for nulliparous women, and 0.6 per thousand for multiparous women. A low Apgar score was registered in 8.6 per thousand births for nulliparous women, and 4.1 per thousand for multiparous women. Conclusions There was a considerable rise in nonurgent referrals to obstetrician‐led care in primary midwife‐led care during labor. Perinatal safety did not improve significantly over time. The persisting rise in referrals challenges the sustainability of the current strict role division between primary and secondary maternity care in The Netherlands.